CORRELATION STUDY OF CHEMOPHOBIA WITH SCIENCE LITERATURE - Herlina, Nina; Ramawati, Atik (Teknosains: Media Informasi Sains dan Teknologi, 2021)
Chemophobia is an irrational fear and anxiety of chemicals or chemicals. Many factors are the cause of chemophobia in addition to the wrong perception in understanding the meaning of the word chemistry itself, one of which is scientific knowledge or scientific literacy (scientific literacy) and many other factors. This study aims to examine the correlation of chemophobia with scientific literacy of students of the 2017 chemistry education study program at UIN Walisongo Semarang. This research is a type of quantitative research using a correlational approach. Participants were taken using a purposive sampling technique, the selection of participants was based on the objectives of the researcher, namely the 2017 class of chemistry education students as many as 27 students. The data sources come from the chemophobia questionnaire and scientific literacy test questions. The Cronbach’s Alpha method was used to test the reliability of the questionnaires and questions of scientific literacy, obtained a reliability value of 0.673 for the chemophobia questionnaire and 0.719 for scientific literacy questions. The research data were analyzed using Speaman Rank correlation with the help of IBM SPSS 25. The results of data analysis showed a correlation value (r) -0.232 a negative sign contained in the correlation value indicated that there was a relationship between the two variables that were not unidirectional, but the sig value. The number 0.244 > 0.05, it can be concluded that there is no significant relationship between chemophobia and scientific literacy.